The Impact of Financial Development on Decarbonization Factors of Carbon Emissions: A Global Perspective - Thangaiyarkarasi, N.; Vanitha, S. (International Journal of Energy Economics and Policy, 2021)
In order to limit the adverse effects of climate change, the carbon dioxide emissions should be controlled. These toxic emissions are associated with the energy sector like coal, oil, natural gas, which produce air pollution and it has to be reduced. Reductions can be brought about by using appropriate technologies and policy initiatives. Financial development has been an important factor, which influences the decision on carbon emissions. This study attempts to study the relationship between financial development and carbon emissions, based on the least square of NLS and ARMA method and the data, based on 10 developed countries and five developing countries, during the study period of 10 years from 1st April 2010 to 31st March 2019. The study employed the Kaya identity IPAT model, unit root test and co-integration test. The variables of GDP per capita and carbon dioxide (CO2) emissions were used as a measure of economic financial development and the status of environmental degradation. Keywords: Carbon dioxide emissions, Financial development, Urbanization, GDP per capita, Climate change, STIRPAT model. JEL Classifications: P44, Q40, Q48, Q54 DOI: https://doi.org/10.32479/ijeep.11872